Attitudes of the Fourth-Grade Primary School Pupils on Learning at Geometry Classes - Olivera J. Đokić (University of Belgrade, Teacher Education Faculty, 2019)
Summary: This paper presents the continuation of the research on the teaching approach of realistic mathematics education (RME) as the second cycle in a successive model of a mixed-method approach. In the first cycle, in the quasi-experimental research with parallel groups, the pupils in the experimental group were taught by using the realistic environment approach, while the pupils in the control group were taught by using the traditional teaching approach. As the effects of the RME approach have been confirmed, this paper aims to determine whether the socio-constructivist environment within the framework of the RME theory, in which a teacher and a textbook play the key role in the construction of knowledge, can have an effect on pupils' attitudes towards learning in geometry classes. Using an open-ended questionnaire, we examined the views of one hundred forty-nine pupils of the fourth grade of primary school on learning at geometry classes. The responses were inductively classified into categories and codes, the meaning of which had been previously indicated, and then we processed the data by using the chi-square technique for comparing the frequency of occurrence of the categories in two groups. We also checked the statistical significance of the obtained differences. The results show that pupils find the realistic environment approach to learning very agreeable, they are more willing to learn, especially to learn with understanding, they have a strong need for active participation in classes, and that they readily accept the innovative model of the textbook from which they learn. We also raised some questions for further research of innovative teaching approaches over a longer period of time to examine the effects of the pupils' long-term evaluation of mathematics